2019
DOI: 10.3390/environments6070081
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Ecology: A Review of Research and Gap Analysis

Abstract: Recreational ecology is an internationally evolving research field addressing the high demand for nature-based tourism and recreation, and its environmental impacts. This review aimed to analyze the research effort of recreational ecology studies published in four renowned journals in the field, the Journal of Sustainable Tourism, Tourism Management, the Journal of Environmental Management, and Environmental Management. Between 1976 and 2017, this review identified 145 papers focused on recreational ecology. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 95 publications
(86 reference statements)
0
21
0
2
Order By: Relevance
“…In their writings, they are much more likely to cite a recent article, so they appear familiar with current literature, than to cite the researchers who originally developed an idea, concept, or finding. Since much of the early work in recreation ecology was published in the grey literature that is seldom cited, or in ecological rather than tourism or environmental management journals (Sumanapala and Wolf 2019), the legacy of the pioneers of recreation ecology is being lost. My hope is that this article will acquaint readers with such pioneers of recreation ecology as "Doc" Meinecke, Neil Bayfield, and Mike Liddle.…”
Section: Discussionmentioning
confidence: 99%
“…In their writings, they are much more likely to cite a recent article, so they appear familiar with current literature, than to cite the researchers who originally developed an idea, concept, or finding. Since much of the early work in recreation ecology was published in the grey literature that is seldom cited, or in ecological rather than tourism or environmental management journals (Sumanapala and Wolf 2019), the legacy of the pioneers of recreation ecology is being lost. My hope is that this article will acquaint readers with such pioneers of recreation ecology as "Doc" Meinecke, Neil Bayfield, and Mike Liddle.…”
Section: Discussionmentioning
confidence: 99%
“…(10) Finally, as recreation ecology investigates the interface between tourists and the environment, research should focus on how to improve visitor experiences so that they marry sustainable resource usage with a sustainable (satisfying) visitor experience. Apart from the studies discussed here (e.g., References [52,54]), such research is largely lacking to date as a research gap analysis in recreational ecology has revealed [25]. For example, research can be directed to answer questions on optimal tour design, such as the best tour group size, the best frequency for repeating the tour at the same location without deterring wildlife, and necessary modifications depending on different tour group compositions (e.g., with clients of different age classes).…”
Section: Future Research Directionsmentioning
confidence: 97%
“…Thus, we exclude adventure 'sports', hunting and fishing, and engagement in research. Research on the environmental impacts of nature-based tourism has biases in habitat (the terrestrial environment is over-represented relative to the marine environment [22]) and geography (USA and Australia are well-represented, whereas Africa and Asia are under-represented [23][24][25]). Thus, the research cited in this review reflects some of these biases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an increase in research in recent decades has improved our knowledge needed for conservation management, but what future research do we need to clarify issues that we still know too little about? Sumanapala and Wolf [6] review 145 articles in four journals relating to environmental management and sustainable tourism. They find Africa and Asia to be underrepresented in the literature, and that aquatic activities such as rafting or diving were studied far less than terrestrial ones such as hiking or wildlife viewing.…”
Section: Highlightsmentioning
confidence: 99%